An Efficient Method for Sterically Demanding Suzuki–Miyaura Coupling Reactions. Issue 7 (7th January 2013) - Zhao, Qing; Li, Chengxi; Senanayake, Chris H.; Tang, Wenjun
<x xml:space="preserve">Abstract</x> An efficient method for sterically demanding Suzuki–Miyaura coupling reactions has been developed with two catalysts, Pd/BI‐DIME (see scheme) and Pd/phenanthrene‐based ligand. The Pd/BI‐DIME catalyst facilitates the syntheses of extremely hindered biaryls bearing ortho‐isopropyl substituents. The other catalyst is efficient for the synthesis of functionalized tetra‐ortho‐substituted biaryls at low catalyst loadings.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>